2008
DOI: 10.1371/journal.pone.0001913
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Phylogenetic Network Methods Using Computer Simulation

Abstract: BackgroundWe present a series of simulation studies that explore the relative performance of several phylogenetic network approaches (statistical parsimony, split decomposition, union of maximum parsimony trees, neighbor-net, simulated history recombination upper bound, median-joining, reduced median joining and minimum spanning network) compared to standard tree approaches, (neighbor-joining and maximum parsimony) in the presence and absence of recombination.Principal FindingsIn the absence of recombination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(99 citation statements)
references
References 40 publications
3
96
0
Order By: Relevance
“…A phylogenetic network was constructed using the software Network version 4.5.1.0 (http://www.fluxus-engineering.com) with a medianjoining algorithm based on maximum parsimony and a 'greedy' method (Bandelt et al, 1999). Under the circumstances of closely related sequences, there are advantages in using a median-joining network to depict relationships (Posada and Crandall, 2001) and simulation studies have demonstrated that this method provides reliable estimates of the true genealogy (Cassens et al, 2005;Woolley et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A phylogenetic network was constructed using the software Network version 4.5.1.0 (http://www.fluxus-engineering.com) with a medianjoining algorithm based on maximum parsimony and a 'greedy' method (Bandelt et al, 1999). Under the circumstances of closely related sequences, there are advantages in using a median-joining network to depict relationships (Posada and Crandall, 2001) and simulation studies have demonstrated that this method provides reliable estimates of the true genealogy (Cassens et al, 2005;Woolley et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A potential avenue could be the use of explicit phylogenetic networks (Huson and Bryant 2006), where one could do the ASR integrating over the different trees embedded in the network, as in Bayesian phylogenetics (Huelsenbeck and Bollback 2001). However, this might be quite challenging given the impact of recombination on the accuracy of phylogenetic networks (Woolley et al 2008) and potential problems identifying the GMRCA (Castelloe and Templeton 1994). An alternative could be the reconstruction of rooted ancestral recombination graphs (Song and Hein 2005;Minichiello and Durbin 2006;Parida et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The search for the 'perfect' phylogenetic tree construction algorithm, based on distance matrices, is still ongoing (Woolley et al, 2008). In the fu- for both methods and all 698 species pairs (i, j).…”
Section: Discussionmentioning
confidence: 99%